METALINGUAL FUNCTION OF LANGUAGE TO AVOID MISUNDERSTANDING IN THE CLASSROOM - Wedananta, Kadek Adyatna; I Gst. Ayu P. Jesika Sita Devi N (Journal of Innovation Research and Knowledge, 2024)
This study seeks to explore the metalingual functions of language to avoid misunderstanding in the classroom. This study employed a qualitative methodology. This research was conducted in schools located in Denpasar, Bali, with teachers and students as its subjects. The metalingual language functions utilized by the teacher and students can be mapped as 40 metalingual functions. From the results of the study, it can be concluded that metalingual function of language function can avoid misunderstanding in the classroom:the metalingual function facilitates communication in the classroom by elucidating the meaning or application of certain codes or words, the metalingual function facilitates the exchange of knowledge regarding language, namely the meaning and grammar of words, by talking about the language itself, the metalingual function might prevent misunderstandings over word usage, and by addressing the language itself, metalingual functions might prevent misunderstandings regarding the meaning of words or codes. it is hoped that future researchers will be able to utilize more samples and studies.